THE NEW WORLD INFORMATION AND COMMUNICATION ORDER DEBATE AND THE DEVELOPMENT OF INFORMATION AND COMMUNICATION TECHNOLOGY IN NIGERIA - BECKY ADE ALIEGBA (International Studies Journal)
While the New World Information and Communication Order (NWICO) debate underlines the centrality of information and communication development to societal transformation in the twenty-first century, it has unarguably led to explosion in human communication in ways previously thought impossible. Yet the media industry in Nigeria as in many parts of the developing world is still gasping for survival. This study serves as a baseline for examining the effectiveness of the NWICO debate, by this, the study identifies areas of weakness in the role that NWICO plays in the Nigerian media for possible improvement. The study was underpinned on the National System of Innovation (NSI) and the News Framing theory, and adopted the mixed research method using historical and content analysis. It also relied on secondary sources of data. The study concluded that NWICO in Nigeria is a work in progress as the gap between the developed countries and the developing is far from being bridged. UNESCO’s presence needs to be felt on the astronomical cost of production inputs and the massive technology disruptions, privacy violation by government or by powerful media houses, proscription of press freedom and the protection of the human rights of journalist. The study recommends the need to unveil policy palliatives to cushion the astronomical cost of production inputs and the massive technology disruptions for the media, to enable practitioners continue to provide affordable and invaluable verified information for the public good. This will hopefully expand the readership base of the mainstream media in terms of affordability and subscriptions.